Effects of trichothecene production by Trichoderma arundinaceum isolates from bean-field soils on the defense response, growth and development of bean plants (Phaseolus vulgaris) - Cardoza, Rosa E.; Mayo-Prieto, Sara; Martínez-Reyes, Natalia; McCormick, Susan P.; Carro-Huerga, Guzmán; Campelo, M. Piedad; Rodríguez-González, Álvaro; Lorenzana, Alicia; Proctor, Robert H.; Casquero, Pedro A.; Gutiérrez, Santiago (Frontiers in Plant Science, 2022)
The trichothecene toxin-producing fungus Trichoderma arundinaceum has potential as a biological control agent. However, most biocontrol studies have focused only on IBT 40837 strain. In the current study, three Trichoderma isolates recovered from bean-field soils produced the trichothecene harzianum A (HA) and trichodermol, the latter being an intermediate in the HA biosynthesis. Based on phylogenetic analysis, the three isolates were assigned to the species T. arundinaceum. Their genome sequences had a high degree of similarity to that of the reference IBT 40837 strain, in terms of total genome size, number of predicted genes, and diversity of putative secondary metabolite biosynthetic gene clusters. HA production by these bean-field isolates conferred significant in vitro antifungal activity against Rhizoctonia solani and Sclerotinia sclerotiorum, which are some of the most important bean pathogens. Furthermore, the bean-field isolates stimulated germination of bean seeds and subsequent growth of above ground parts of the bean plant. Transcriptomic analysis of bean plants inoculated with these T. arundinaceum bean-field soil isolates indicated that HA production significantly affected expression of plant defense-related genes, being this effect particularly significant in the level of expression observed for the chitinase encoding genes. Together, these results would emphasize in the interest to search for Trichoderma species able to produce non-toxic trichothecenes, as tools to induce plant defenses without negatively affecting their germination and development